The Effect of One Period Factitious and True Neurofeedback Training on the Balance Performance of Active Males - Amir Hossein Barati; Asghar Mahmoudi; Vida Farhan; Gholam Reza Lotfi (Biyumikānīk-i varzishī)
Objective: The main objective of the study was to investigate the effect of factitious and true neurofeedback training on the balance performance of active males. Methods: Twenty physical education male students were selected through purposive sampling and were randomly divided into real neurofeedback and sham neurofeedback groups (with mean age 21.38±1.32 years and mean weight of 71.01±3.58 and mean height 173.88±4.69cm). The participants attended neurofeedback training session 3 times a week for a period of one month. Prior to and after training, pre-test and post-test of static balance, semi balance and dynamic balance were administered using Bass Stick, Modified Romberg and Y test. Repeated measures ANOVA was run at a significance level of p<0.05 to analyze the data. Results: Results showed that real neurofeedback training would have significant impact on static balance, semi balance and dynamic balance participants (Except for dorsolateral). The means of static balance and semi balance 4.19 and 3.72 seconds and dynamic balance on anterior direction 13.89 cm and on medial posterior 6.59 cm were increased, respectively. Conclusion: Due to its positive impact on the balance of active males, neurofeedback training can be used as a complementary training program to increase their efficiency of such students in competitions.